Understanding Indigenous patient attendance: A qualitative study. (22nd June 2017) - Copeland, Stephen; Muir, Josephine; Turner, Angus
Abstract: Objective: To better understand Indigenous patient non‐attendance at medical specialty appointments by learning from the patients attending their scheduled outreach ophthalmology clinic appointment. Design, setting and participants: A qualitative study using face‐to‐face, semi‐structured interviews with 69 Indigenous Australian ophthalmology patients and 8 clinic workers at one urban and one rural Aboriginal Medical Service (AMS) over the period from April 2015 to November 2015. Main outcome measures: Explored motivations and enablers for attending patients to guide best practice for specialist outreach clinics. Results: The main themes emerging from the interviews included: clinic staff are persistent in their efforts to organise outreach ophthalmology clinics; both motivated and reluctant patients attend medical appointments; and reluctant patients are more likely to be unaware of their referral pathway. Health literacy and clinic staff triggered the reluctant patient to attend. Conclusion: Indigenous patients attend their outreach ophthalmology appointments based on various motivations. Clinic staff who recognise reluctant patients can communicate through a sensitive, patient‐centred approach that helps the patient realise the importance of the appointment thus creating motivation and promoting attendance. The efforts of the clinic staff, through their patient reminding, transport provision and patient‐centred communication suggest that they are the enablers of Indigenous patient attendance at AMS outreach ophthalmology clinics.